2010
DOI: 10.1177/1947601910392987
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Receptor Flt/VEGFR Family: Its Characterization Related to Angiogenesis and Cancer

Abstract: Ligands and their tyrosine kinase (TK) receptors regulate a variety of biological systems in animals. Vascular endothelial growth factor (VEGF) and its receptor (Flt/VEGFR family) system play a crucial role not only in physiological but also in most parts of pathological angiogenesis including cancer. Flt-1/VEGFR-1 and KDR/VEGFR-2 bind VEGF-A but have different functions on angiogenesis at early embryogenesis: Flt-1 has a negative role by trapping ligands, whereas KDR (Flk1 in mice) exerts a strong positive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 39 publications
2
46
1
1
Order By: Relevance
“…VEGF, particularly VEGF-A, is a key factor promoting angiogenesis by binding with its receptors, VEGFR-1 and VEGFR-2. VEGFR-2 has a more dominant role in angiogenesis, while VEGFR-1 is involved mainly in the migration of macrophages and vascular endothelial cells (15). VEGF activates VEGFR and the downstream phosphoinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK)/ERK1/2 signaling pathways (16,17) and promotes angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF, particularly VEGF-A, is a key factor promoting angiogenesis by binding with its receptors, VEGFR-1 and VEGFR-2. VEGFR-2 has a more dominant role in angiogenesis, while VEGFR-1 is involved mainly in the migration of macrophages and vascular endothelial cells (15). VEGF activates VEGFR and the downstream phosphoinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK)/ERK1/2 signaling pathways (16,17) and promotes angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…AGE is important in diabetic retinopathy, particularly in PDR (14,15). It is reported that AGE promotes neovascularization by increasing the expression of VEGF (mainly VEGF-A) in endothelial cells and consequently inducing tube formation of the retinal microvessel endothelial cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear explanation is available due to conflicting results regarding the influence of VEGF-KDR signaling on blood vessels as well as the complex roles of VEGF-KDR signaling [24][25][26][27][28][29][30][31][32]. VEGF-KDR system plays a critical role not only physiological but also in most parts of pathological angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of VEGF-A include endothelial cell proliferation, survival, migration, invasion, chemotaxis of bone marrow progenitors, vascular permeability, and vasodilation, which are mediated by its binding and activation of receptor tyrosine kinases VEGFR-1 and VEGFR-2 (Ellis and Hicklin, 2008). Although VEGF-A binds VEGFR-1 with approximately 10 times higher affinity than VEGFR-2, the higher kinase activity of VEGFR-2 makes it the most important effector of VEGF-A signaling (Shibuya, 2010;Shalaby et al, 1995). VEGF-A is the best-characterized member of the VEGF family.…”
Section: Angiogenesis Pathways Antiangiogenic Agents and Their Effecmentioning
confidence: 99%
“…Aflibercept is a soluble recombinant fusion protein designed to block the angiogenesis network binding to all isoforms of VEGF and to placental growth factor (Kim et al, 2002a;Holash et al, 2002). It developed by fusing sections of second immunoglobulin (Ig) domain of VEGFR-1 and the third Ig domain of VEGFR-2 to the Fc portion of human IgG (Shibuya, 2010;Inai et al, 2004;Huang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%